Disposed to Be Overconfident - Katrin Gödker; Terrance Odean; Paul Smeets (Center for Economic Studies and ifo Institute (CESifo), 2023)
We show that the disposition effect–the tendency of investors to hold losers and sell winners–can be a source of overconfidence. We find experimental evidence that individuals update beliefs about their own investment ability based on realized gains and losses rather than the overall performance of their portfolio. We also find supporting field evidence. Dutch retail investors who realized more gains than losses believe they have higher portfolio performance relative to other investors, even after controlling for their actual portfolio performance. We develop a formal model demonstrating how the disposition effect leads to overconfidence and examine model implications for investors' trading behavior and expected profit.
Keywords: D01; G40; 330; investor beliefs; disposition effect; overconfidence; experimental finance